HPTLC and FTIR Fingerprinting of Olive Leaves Extracts and ATR-FTIR Characterisation of Major Flavonoids and Polyphenolics - Snezana Agatonovic-Kustrin (MDPI AG, 2021)
The aim of this study was to analyse the effect of spontaneous microbial maceration on the release and extraction of the flavonoids and phenolics from olive leaves. Bioprofiling based on thin-layer chromatography effect-directed detection followed by ATR-FTIR spectroscopy proved to be a reliable and convenient method for simultaneous comparison of the extracts. Results show that fermentation significantly enhances the extraction of phenolic compounds and flavonoids. The polyphenolic content was increased from 6.7 µg GAE (gallic acid equivalents) to 25.5 µg GAE, antioxidants from 10.3 µg GAE to 25.3 µg GAE, and flavonoid content from 42 µg RE (rutin equivalents) to 238 µg RE per 20 µL of extract. Increased antioxidant activity of fermented ethyl acetate extracts was attributed to the higher concentration of extracted flavonoids and phenolic terpenoids, while increased antioxidant activity in fermented ethanol extract was due to increased extraction of flavonoids as extraction of phenolic compounds was not improved. Lactic acid that is released during fermentation and glycine present in the olive leaves form a natural deep eutectic solvent (NADES) with significantly increased solubility for flavonoids.